1982
DOI: 10.1111/j.1752-0606.1982.tb01444.x
|View full text |Cite
|
Sign up to set email alerts
|

Female‐headed Families: Effects on Children and Clinical Implications*

Abstract: The social psychological research pertaining to female‐headed families published between 1970–1980 is reviewed. The literature indicates that theoretically children do not need the presence of the same‐sex/opposite‐sex parents in the family in order to develop sex‐role behavior. Children in female‐headed families are likely to have good emotional adjustment, good self‐esteem except when they are stigmatized, intellectual development comparable to others in the same socioeconomic status, and rates of juvenile d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

1984
1984
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…(See Hetherington, Camara, &Featherman, 1983, andShinn, 1978, for reviews of this literature.) These studies have generally concluded that these differences were the result of the relative economic disadvantage of those from single parent backgrounds (Bachman, O'Malley, & Johnston, 1978;Cashion, 1982;McLanahan, 1985).…”
Section: Single Parent Family Background and The Transition To Adulthoodmentioning
confidence: 97%
“…(See Hetherington, Camara, &Featherman, 1983, andShinn, 1978, for reviews of this literature.) These studies have generally concluded that these differences were the result of the relative economic disadvantage of those from single parent backgrounds (Bachman, O'Malley, & Johnston, 1978;Cashion, 1982;McLanahan, 1985).…”
Section: Single Parent Family Background and The Transition To Adulthoodmentioning
confidence: 97%
“…In sum, it is very simplistic to point to the divorce per se as the causal link in positive or negative adjustment, an approach that may account for why prior studies comparing children from divorced and intact families have found no consistent findings in adjustment (Lowery & Settle, 1985). A host of intervening variables other than the parental separation are involved, including age of child, circumstances and preparation for divorce, availability of support, material resources, interparental conflict, and cultural, familial, and individual beliefs and attitudes (Atwood, 1993;Cashion, 1982), as well as the social expectancies and confirmations set up by researchers and practitioners in the field.…”
Section: Mothers Responsiblementioning
confidence: 99%
“…All of the studies have some serious limitations and are therefore unsuitable for a current assessment of our knowledge of the broken home/delinquency relationship. Cashion (1982), for instance, reviewed the research on female-headed families and delinquency and concluded that there is no association between this type of family structure and delinquency in general. Nevertheless, this conclusion was predicated on a total of eight studies, all of which were published in the 1970s.…”
mentioning
confidence: 97%